Model of Sustainable Community Participation in Homestay Program - Wan Abd Aziz, Wan Mohd Amin (Mediterranean Centre of Social and Educational Research, 2015)
Tourism is one of the important sectors contribute to the world economic growth according to the World Tourism Organization (UNTWO). The increase of international tourists arrival from 438 million in 1990 to 940 million in 2010 or 114.6 percentage show that the tourism sector has become a potential sector in providing a huge job market to the people. Referring to (UNWTO, 1998) the tourist arrivals are expected to increase 4.4 percent between years 2010 to year 2020. The aim of this study is to develop model of sustainable community participation in homestay program. A total of 306 respondents were selected using a stratified random sampling based on number of participants in the homestay program from several locations in Malaysia. All the data were analyzed using structural equation modeling (SEM). This study successfully developed fit model between community participation and sustainable development among the homestay participants. Finding from present study indicate that community participation in community-based tourism has influenced to the sustainable development among the homestay participant in the study area.